Block structure of physical training for Сhinese volleyball students - Shenlun, Tian; Bulykina, L.V.; Nikolaeva, I.V.; Pleshakov, A.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to develop and justify a comprehensive physical training system for Chinese volleyball players aged 17-19. Methods and structure of the study. The work included theoretical development of the problem-oriented block, the pedagogical impact block, the procedural and results-assessment blocks of comprehensive physical training within the framework of a formative experiment (2023-2024) with volleyball players from Chinese university teams (n=64). Results and conclusions. The implementation of the problem-oriented block, the block of pedagogical impact block, the procedural and effective evaluation blocks allows optimizing the content of comprehensive physical training of volleyball players of Chinese university student teams.